Photocatalytic activity of nanoparticles: the development of the standardized measurement for physiological conditions. Issue 9 (26th November 2022) - Reipa, Vytas; Song, Nam Wong; Kwak, Minjeong; Heo, Min Beom; Lee, Tae Geol; Westerhoff, Paul; Bi, Yuqiang; Toman, Blaza; Hackley, Vincent A.; Kato, Haruhisa; Tabei, Yosuke; Nontapot, Kanokwan; et al.
Abstract: Recently a new International Standard for testing nanomaterial photocatalytic activity under physiological conditions was issued by Technical Committee 229 (Nanotechnologies) of the International Organization for Standardization (ISO 20814:2019 Nanotechnologies-Testing the photocatalytic activity of nanoparticles for NADH oxidation). The document offers a robust, high throughput photocatalytic assay using a bio-compatible indicator nicotinamide amide dinucleotide (NAD) and provides a screening tool to gauge nanomaterial potency for phototoxicity. This paper describes the measurement principles behind this assay, the scope of the standard and its validation through an interlaboratory comparison study using a traceable standard reference material (SRM 1898).